Penerapan Islamic Platform Sistem Informasi Manajemen Masjid di Lingkungan PCM Karangploso Malang - Setyawan, Novendra; Nasar, Muhammad; Zulfatman, Zulfatman; Fajar, Dwi Nur (Universitas Nusantara PGRI Kediri, 2021)
KH. Ahmad Dahlan’s Mosque is a mosque that was founded in 2012 in Ngijo village, Karangploso sub-district under the auspices of the Muhammadiyah branch of Karangploso. Good mosque management besides having supporting facilities and infrastructure, to provide good service to the congregation, of course the mosque must have good data and congregational data collection systems as well. That is what the management of the KH mosque complained about. Ahmad Dahlan, who has difficulty managing data for mosque congregations and business charities. Based on these problems, this community service designs and implements a website-based Islamic mosque management information system software that can handle problems and serve as partner management data.